The Interplay of Financial Exchanges and Offline Interpersonal Relationships through Digital Peer-to-Peer Payments. (October 2021) - Li, Lingyuan; Freeman, Guo; Wohn, Donghee Yvette
Highlights: In financial exchanges, awkwardness can be reduced through peer-to-peer payments. Perceived fairness is stronger via peer-to-peer payments in financial transactions. Peer-to-peer payments build trust and relieve tensions in interpersonal relationships. Peer-to-peer payments may heighten peer pressure and cause the loss of emotion. Abstract: Financial transactions play a critical role in people's interpersonal relationships since money is a sensitive and complex component of everyday life. In particular, emerging digital peer-to-peer (P2P) payment applications further complicate how people deal with each other regarding money. Yet, there is a lack of empirical evidence on how and why such technology may lead to new and more complex influences on people's offline interpersonal relationships. Using 23 in-depth interviews, this paper explores the influences of using digital P2P payments on people's experiences of interpersonal financial exchanges and their offline interpersonal relationships. Our findings show that using digital P2P payments helps reduce awkwardness and ensure a stronger sense of fairness in financial exchanges. In addition, though digital P2P payments can relieve tension and reduce distrust in users' interpersonal relationships, they also result in loss of emotion and increase peer pressure. We extend existing studies on computer-mediated interpersonal relationships by highlighting the important role of the complicated technology-mediated financial exchanges in perceiving, shaping, and approaching today's offline interpersonal relationships. We also propose potential design implications for designers and developers to take such an interplay of financial exchanges and interpersonal relationships into consideration to design more supportive and socially satisfactory digital P2P payment platforms in the future.